(3CNHGQ GdHMJQj hTYQgs - (3GdHMJQj , CHh YHGOI GdhdjO Hf YHjO Hf jMji GdWGFj GdHMJQj, GdHMJQj,J (B284 (3g` s
(3ChdgG (B:s
"(3CdqeJ hgd EdeGegG dc fGaY(B" s
(3BNQgG (B:s
(3jSehfg HGSe GdNdjaI HYOeG QYi GdVCf ajge PG eTjH hCeQOG s
(3hgh eNWhW jJVef ChdkG CHhGHkG ef CNHGQ GdoHMJQjs
(3Ke jCJj OjhGfg oeQJHkG bhGajg Ydi MQha GdgLGAs
(3hHChdg hBNQg fbhds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B9 - (3U (B141s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B7 s
Keywords: (3GdCOHs